Seismic behavior and cross-scale refinement model of damage evolution for RC shear walls. (15th July 2018) - Dong, Yao-Rong; Xu, Zhao-Dong; Zeng, Ke; Cheng, Yu; Xu, Chao
Highlights: The refinement model of damage evolution realizes the cross-scale conversion of damage information about structural components of RC shear walls from the local material scale to the component scale. Abstract: The influence on the seismic behavior of RC shear walls by axial loads is evaluated and the observed damage in the earthquake damage investigation of RC shear walls is reproduced in this paper. Six RC shear walls with aspect ratio of 2 were analyzed by the method of nonlinear finite element under different axial load ratios, and the suggested modeling techniques and the accuracy of the numerical method were verified. The seismic performance of shear walls including load–displacement responses, ductility performance, stiffness degradation and energy dissipation capacity were discussed. The analysis results indicate that axial load has a significant effect on the seismic performance of RC shear walls. On the basis of this, the qualitative and quantitative relationships between the development of material damage and the deterioration of component performance were analyzed. It realizes the cross-scale conversion of damage information about structural components of RC shear wall from the local material scale to the component scale. Then the cross-scale refinement model of damage evolution of RC shear walls in the whole process was established, simplified and verified. The results show that, the refinement model can explain the development and distribution of damage evolution of RC shear walls in the whole process quickly and easily. The research results can provide a reference for the refinement of seismic design, damage assessment and reinforcement of RC shear walls.